010101 : Art in Technological Times. - Betsky, Aaron; Bishop, Janet; Davis, Erik; Forde, Kathleen; Gagnon, Adrienne; Pollace, Pam; Ross, David A.; Toop, David; Weber, John S.; Weil, Benjamin (San francisco : San Francisco Museum of Modern Art, 2001)
Adigard, Erik ; Appel, Kevin ; Asymptote - Hani Rashid & Lise Anne Couture ; Baranowsky, Heike ; Begerow, Annette ; Blake, Jeremy ; Bollinger, Rebeca ; Cardiff, Janet ; Chafe, Chris ; Niemeyer, Greg ; Davies, Char ; Décosterd, Jean-Gilles ; Rahm, Philippe ; Droog Design ; Eno, Brian ; Entropy8Zuper! ; Finley, Chris ; Graham, Rodney ; Gursky, Andreas ; Hendricks, Jochem ; Hu Jie Ming ; Kalpakjian, Craig ; Lee Bul ; MacDonald, Euan ; Maeda, John ; Miyajima, Tatsuo ; Napier, Mark ; Paine, Roxy ; Rashid, Karim ; Ritchie, Matthew ; Ross, Adam ; Sander, Karin ; Sze, Sarah ; Thomson, John ; Craighead, Alison ; Tse, Shirley ; Yuan Goang-ming
biog., catalogue of the exhibition p. 146-151
Engels
010101 : Art in Technological Times, San Francisco Museum of Modern Art, San Francisco, March 3 to July 8, 2001
boek